2023
DOI: 10.1111/andr.13406
|View full text |Cite
|
Sign up to set email alerts
|

Low‐intensity pulsed ultrasound ameliorates erectile dysfunction induced by bilateral cavernous nerve injury through enhancing Schwann cell‐mediated cavernous nerve regeneration

Abstract: Background Cavernous nerve injury‐induced erectile dysfunction caused by pelvic surgery or trauma is refractory to conventional medications and required an alternative treatment. Low‐intensity pulsed ultrasound is a noninvasive mechanical therapy that promotes nerve regeneration. Objectives To investigate the therapeutic effect and potential mechanism of low‐intensity pulsed ultrasound in the treatment of neurogenic erectile dysfunction. Materials and methods Thirty rats were randomly divided into the sham‐ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…found that LIPUS could increase testosterone levels in animal models and alleviate Leydig cell aging in vitro ( 51 ). Furthermore, combining LIPUS with tadalafil effectively treats erectile dysfunction in patients with type 2 diabetes ( 52 ), and promotes nerve regeneration and improves erectile function by enhancing Schwann cell proliferation, migration, and expression of neurotrophic factors such as nerve growth factor ( 53 ). In terms of bone metabolism, Wu et al.…”
Section: Discussionmentioning
confidence: 99%
“…found that LIPUS could increase testosterone levels in animal models and alleviate Leydig cell aging in vitro ( 51 ). Furthermore, combining LIPUS with tadalafil effectively treats erectile dysfunction in patients with type 2 diabetes ( 52 ), and promotes nerve regeneration and improves erectile function by enhancing Schwann cell proliferation, migration, and expression of neurotrophic factors such as nerve growth factor ( 53 ). In terms of bone metabolism, Wu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Ectoderm, mesoderm, and endoderm are the three germ cells that can be differentiated from iPSCs, similar to ESCs, in contrast to MSCs, which can only differentiate into a limited number of cell lines [86]. Increases in ICP/MAP, eNOS, and S100β content in MPG can be achieved by employing iPSCs to repair cavernous nerve integrity [87].…”
Section: Induced Pluripotent Stem Cells (Ipscs) On Edmentioning
confidence: 99%